2016
DOI: 10.1088/0143-0807/37/5/055305
|View full text |Cite
|
Sign up to set email alerts
|

Inexpensive Mie scattering experiment for the classroom manufactured by 3D printing

Abstract: Scattering experiments are fundamental for structure analysis of matter on molecular, atomic and sub-atomic length scales. In contrast, it is not standard to demonstrate optical scattering experiments on the undergraduate level beyond simple diffraction gratings. We present an inexpensive Mie scattering setup manufactured with 3D printing and open hardware. The experiment can be used to determine the particle size in dilute monodisperse colloidal suspensions with surprisingly high accuracy and is, thus, suitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…[13][14][15] In experiments with colloids, spinners driven by magnetic fields can generate chaotic fluid flow reminiscent of turbulence, 16 while electric fields can be used to assemble Janus particles into rotating pinwheels which may synchronize their rotation direction. 17 Active spinning may also be achieved in vibrated granular materials, [18][19][20][21][22] through the use of asymmetric particles driven by the shaking of a quasi-two-dimensional container. These studies have demonstrated that spinning particles display some key thermal-like properties, since the translational degrees of freedom are no longer actively-or boundary-driven: the particles only acquire translational momentum through either collisions or hydrodynamic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] In experiments with colloids, spinners driven by magnetic fields can generate chaotic fluid flow reminiscent of turbulence, 16 while electric fields can be used to assemble Janus particles into rotating pinwheels which may synchronize their rotation direction. 17 Active spinning may also be achieved in vibrated granular materials, [18][19][20][21][22] through the use of asymmetric particles driven by the shaking of a quasi-two-dimensional container. These studies have demonstrated that spinning particles display some key thermal-like properties, since the translational degrees of freedom are no longer actively-or boundary-driven: the particles only acquire translational momentum through either collisions or hydrodynamic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…As described in the literature, we also observe orientational fluctuations, caused by an instability of the driving mechanism to the microscopic surface roughness, and inertial delay effects due to the mass of the particles 47,57 . When vibrobots are excited above a certain amplitude threshold, they begin to tumble 58 . As a result, they randomly reorient while moving and eventually change the direction of their path.…”
Section: Resultsmentioning
confidence: 99%
“…When placed on a vertically vibrating table, these particles transfer vibrational energy into rotation through an interplay of friction, inertial forces, and inelastic interaction between the particle and the vibrating table [28,29]. The motion of the particles depends on the vibration parameters and characteristics of the vibrot such as number and inclination of legs, total mass, and others [28,30]. It was shown that a gas of such particles has very similar properties to a homogeneously heated granular gas [31].…”
Section: Methodsmentioning
confidence: 99%
“…Here we study the opposite limit of a granular gas: we consider a gas of particles that rotate and exchange angular momentum while the translational degrees of freedom are suppressed. Our experimental system is comprised of interacting rotators, called vibrots [27][28][29][30][31][32], whose spatial positions are fixed on a lattice. We analyze the impact of particle interactions on the system's overall dynamics and the role of collective modes.…”
Section: Introductionmentioning
confidence: 99%